Spatial energy channelling and stochastization of fast ion motion by high-frequency plasma instabilities - Tyshchenko, M.H.; Yakovenko, Yu.V. (Вопросы атомной науки и техники, 2015)
The conditions are established when multiple Alfvén eigenmodes are able to withdraw a significant part of the energy of fast ions for possible transfer to another spatial region (spatial channelling). This can happen when the resonance islands of the instabilities overlap to form an extensive stochastic zone in the fast ion phase space. An analytical expression for the width of a resonance island induced by an Alfvén eigenmode in the phase space is derived. The number and amplitude of modes are estimated, which are required to form a stochastic zone in a given energy range. Two codes intended for numerical verification of these estimates are briefly described. First results of these codes are presented.